THE AUTHORITY OF THE CONSTITUTIONAL COURT OF THE REPUBLIC OF INDONESIA WITHIN THE SCOPE OF THE INDONESIAN CONSTITUTIONAL LAW SYSTEM - Muhammad Rangga (Journal of Governance and Law Reform, 2026)
This study aims to analyze the legal basis, scope of authority, and implications of the authority of the Constitutional Court of the Republic of Indonesia within Indonesia’s constitutional legal system. This research employs a normative legal research method using a statutory approach, conceptual approach, and case approach. The legal materials consist of primary, secondary, and tertiary legal sources collected through library research and subsequently analyzed qualitatively using deductive reasoning. The findings indicate that the authority of the Constitutional Court has a strong constitutional foundation, as stipulated in Article 24C of the 1945 Constitution of the Republic of Indonesia and Law Number 24 of 2003 concerning the Constitutional Court, as most recently amended by Law Number 7 of 2020. Such authority includes reviewing laws against the 1945 Constitution of the Republic of Indonesia, resolving disputes concerning the constitutional authority of state institutions, deciding on the dissolution of political parties, resolving disputes over general election results, and rendering decisions on the opinion of the House of Representatives regarding alleged violations committed by the President and/or Vice President.This study concludes that the Constitutional Court plays a strategic role as the guardian of the constitution in upholding constitutional supremacy, strengthening the system of checks and balances, protecting citizens’ constitutional rights, and promoting the establishment of a democratic, equitable constitutional legal system.